Analisis Yuridis Regulasi Perlindungan Konsumen terhadap Iklan Menyesatkan Berbasis Data di Platform Tiktok - Widya Chantika Tria Amanda Amanda (Jurnal Hukum Lex Generalis, 2025)
This research was conducted in the context of the rapid development of digital technology that is changing the way companies interact with consumers, particularly through data-driven advertising on the TikTok platform, which has the potential to give rise to misleading advertising practices and serious consumer protection risks. The main objective of this research is to analyze the legal regulations in Indonesia regarding consumer protection against misleading data-driven advertising on TikTok, and to evaluate the effectiveness and need for strengthening existing regulations. The method used is a library research with a normative juridical approach, utilizing primary data in the form of laws and regulations and secondary data from legal literature and official reports to conduct a descriptive-qualitative analysis. The main findings reveal that current regulations are unable to anticipate the complexity of TikTok's algorithm and the challenges of data transparency, resulting in less effective oversight and law enforcement. This study makes an important contribution to an integrative understanding of technological, legal, and ethical aspects in the context of digital advertising, highlighting the need for increased algorithm transparency, law enforcement capacity, and active consumer participation. In conclusion, the implementation of consumer protection regulations must be adaptive and collaborative, combining legal, technological, and educational aspects to create a fair and accountable digital advertising ecosystem. This research also recommends the development of technology audit mechanisms and regulations that are responsive to digital dynamics for optimal consumer protection.